Morphological Characteristics of European Slalom Canoe and Kayak Paddlers - Coufalová,Klára (Sociedad Chilena de Anatomía, 2021)
SUMMARY: The primary aim of this study was to determine the morphology of elite canoe slalom paddlers and to identity if morphology differences existed between kayak and canoe paddlers. The survey included a total of 74 canoe slalom paddlers who competed in the 2018 European Championship. These competitors were assessed using a battery of anthropometric dimensions according to standardized anthropometric techniques and bioimpedance analysis using the multifrequency octopolar device Tanita MC-980. Elite slalom male competitors can be characterized to having average body height (~180 cm), average weight (~75 kg), with ectomorphic mesomorph somatotype (1.3 - 5.5 - 2.7), well developed trunk and arm muscles (biceps girth: 35.4 ± 1.8), low hypertrophy of legs and low body fat (8 ± 3.2 %). In addition, there are no significant differences between canoe (C1) and kayak (K1) paddlers. For female competitors we can conclude, there has been little change in anthropometric values through the decades. However, C1 competitors are younger, more mesomorphic and less ectomorphic.